Distributive Justice and Maqāṣid al-Sharīʿah in Islamic Disaster Relief: A Comparative Analysis of Beneficiary Targeting in Aceh Tamiang and Batu Busuak Flood Response Programs - Dirja Hasugian; Fachri Rinaldy (Program Studi Hukum Ekonomi Syariah STAI As-Sunnah Deli Serdang, Sumatera Utara, 2026)
This article examines the distributive justice dimensions of Islamic disaster relief operations through a comparative analysis of two flood response programs in Indonesia: the Aceh Tamiang intervention (November 2025) coordinated by STAI As-Sunnah Deli Serdang, and the Batu Busuak, Padang response (December 2025) implemented through Singapore-Indonesia Islamic philanthropy collaboration. Drawing on empirical data from both case studies, this research investigates how beneficiary targeting mechanisms align with the principles of maqāṣid al-sharīʿah, particularly ḥifẓ al-nafs (preservation of life) and the Islamic conception of ʿadl (justice). The methodology employs a qualitative comparative approach, extracting and systematizing empirical indicators of targeting accuracy, vulnerability categorization, and dignity preservation from field reports. Findings reveal that both programs employed tiered beneficiary classification systems responsive to damage severity, yet demonstrated divergent approaches to reaching vulnerable subpopulations. The Batu Busuak program explicitly categorized households by damage level (swept away, severely damaged, general recipients), while the Aceh Tamiang response utilized multi-location distribution with adaptive delivery methods. Both cases evidence tension between operational efficiency and individualized need assessment—a challenge with significant implications for shariah governance of humanitarian aid. This article contributes to Islamic economic law scholarship by proposing a maqāṣid-based evaluative framework for assessing distributive justice in disaster philanthropy, offering policy recommendations for enhanced targeting protocols grounded in Islamic legal ethics.